Eficácia de cinco protocolos de descontaminação final contra enterococcus faecalis e seus efeitos na resistência de união do material obturador à dentina - Lana, Daniel de Lima Dalla (2016)
Introduction: The aim of this study was evaluate the effectiveness of five final decontamination protocols against Enterococcus faecalis and its effects on bond strength of filling material to root canal dentin. Methods: Ninety human roots standardized in 15 mm of length were prepared with ProTaper system, divided randomly in six groups and sterilized. Sixty roots (n=10) were inoculated with Enterococcus faecalis and submitted to the following protocols: 1- distilled water (control), 2- 2% chlorhexidine solution, 3- QMix, 4- 6.5% grape seed extract, 5- photodynamic therapy with optical fiber and 6- photodynamic therapy without optical fiber. The percentage of reduction of CFUs was checked and SEM images were obtained to illustrate the bacterial reduction. The remaining 30 samples were submitted to the same protocols (n=5), filled and used to push out. One-way ANOVA test was applied separated in the microbiological and push out tests, followed by Tukey s HSD post hoc procedure, at a significance level of 5%. Results: The greater bacterial reduction was observed for 2% chlorhexidine, QMix and 6.5% grape seed extract, with no statistically significant difference between them. Photodynamic therapy, with and without optical fiber, showed a significantly higher reduction than distilled water (p<0.05). For the push out test, final decontamination protocols showed similar bond strength values (P>0.05). Conclusion: 2% chlorhexidine, QMix and 6.5% grape seed extract were more effective than photodynamic therapy against Enterococcus faecalis. Furthermore, the final decontamination protocols did not affect the bond strength values.